Plasmin enzymatic activity in the presence of actin - Yusova, E.I. (Вiopolymers and Cell, 2015)
Aim. To study the changes in the plasmin activity towards substrates with high and low molecular mass in the presence of actin. Methods. The proteins used for this investigation were obtained by affinity chromatography and gel-filtration. The plasmin enzymatic activity was determined by a turbidimetric assay and a chromogenic substrate-based assay. The enzyme linked immunosorbent assay and biotin-avidin-phosphatase system were used to study the interaction of plasminogen and its fragments with actin. Results. It was shown that G-actin causes 1.5-fold decrease in the rate of polymeric fibrin hydrolysis by plasmin and Glu-plasminogen activated by the tissue plasminogen activator. However, actin did not impede plasmin autolysis and had no influence on its amidase activity. We have studied an interaction of biotinylated Glu-plasminogen and its fragments (kringle 1-3, kringle 4 and mini-plasminogen) with immobilized G-actin. Glu-plasminogen and kringle 4 had a high affinity towards actin (C50 is 113 and 117 nM correspondingly). Mini-plasminogen and kringe 4 did not bind to actin. A similar affinity of Glu-plasminogen and kringle 1-3 towards actin proves the involvement of the kringle 1-3 lysine-binding sites of the native plasminogen form in the actin interaction. Conclusions. Actin can modulate plasmin specificity towards high molecular mass substrates through its interaction with lysine-binding sites of the enzyme kringle domains. Actin inhibition of the fibrinolytic activity of plasmin is due to its competition with fibrin for thelysine binding sites of plasminogen/plasmin.